NS2 based performance comparison study between DSR and AODV protocols - Fahad, Ahmed Mohammed; Alani, Sammer; Mahmood, Sarmad Nozad; Fahad, Nadia Mohammed (The World Academy of Research in Science and Engineering, 2019)
Mobile AD-HOC Network (MANETs) are useful when no traditional communication infrastructure exists, and have applications in military and other fields; MANET is a set of nodes capable of communicating with each other irrespective of infrastructure or centralized management. The mobility of system nodes leads them to be arranged and designed automatically. In addition, wireless networks have received extensive attention in the fields of communication systems owing to their prospective applications in different fields such as military, industrial and private area networks. Moreover, wireless networks are easy to install, inexpensive, reliable, and do not need a fixed infrastructure, unlike the wired networks. In the MANETs, routing protocols play an essential role to discover the ways between the source and the destination. Generally, an appointed routing protocol system aims to address the difficulties of the progressively evolving topologies. It is possible to divide MANET routing protocols into three kinds: proactive, receptive and hybrid. In this report, routing protocol topology such as queue size and a number of nodes was altered and the efficiency metrics of two reactive routing protocols such as Ad hoc On-Demand Distance Vector AODV and Dynamic Source Routing DSR were contrasted in terms of average end-to-end delay, average throughput and packet delivery ratio.